Giardia duodenalis Infections in Humans and Other Animals in China - Li, Junqiang; Wang, Haiyan; Wang, Rongjun; Zhang, Longxian (Frontiers in Microbiology, 2017)
Giardia duodenalis is an important zoonotic pathogen of public and veterinary health. G. duodenalis has been genotyped into at least eight assemblages (A–H), each with a distinct host range. In recent years, this intestinal protozoan parasite has been identified widely in humans and various other animals, and even exist in environmental contaminants. Along with the whole genome sequence for G. duodenalis, multi-locus sequence typing is being used increasingly to characterize the G. duodenalis. Here, we review the epidemiology, genotyping and subtyping of G. duodenalis in humans and in a wide range of animals, even in wastewater, in China.